"Belatedly, Asia's Literary Scene Comes of Age": Celebratory English Discourse and the Translation of Asian Literature - Aveling, La Trobe University, Australia, Harry (Asiatic: IIUM Journal of English Language and Literature, 2008)
On 8 November 2007, the International Herald Tribune (IHT) triumphantly announced thatÂ â€œbelatedly,â€ the Asian literary scene had â€œcome of age.â€ There were two reasons for this belated success. The first was that an increasing number of literary works by Asian authors are now appearing in English or in English translations. The other was that major British and, especially, American publishing companies are now establishing branch companies in this region.Â  Â Â Â  This paper will examine the discourse of the IHT article to suggest how celebratory English language constructs a particular view of literary success â€“ success in terms of a dominant international English. This analysis will be framed within a wider context of Postcolonial Translation Studies.